Ketahanan Pakan melalui Silase untuk Ternak Domba di Kecamatan Takokak, Kabupaten Cianjur - Billyardi Ramdhan; . Suhendar; Endang Tri Astutiningsih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
The society at Takokak Sub-District, Cianjur have the fresh green feed issued which are limited in dry season. This society services with the aim for giving socialization and skill about silage feed technology for a group of sheep cattlemen have been done. This program was conducted with Participatory Rural Appraisal (PRA) method which involves the society in planning and implementating the program. There are six program, as followed; 1) Choosing the member; 2) Socialization the program; 3) Training; 4) Making the silage; 5) Applying silage feed; and 6) Monitoring and evaluating. The society is very enthusiastic in implementating the program. There are six results gained from the implementation of this program, such as; 1) The society involvement was plenty enough; 2) Formed of piloting group who become the cadre and manager of “silage house”; 3) The participants knowledge increased after having socialization and training of making silage.; 4) The society could make a good standard silage which is convinient for the cattle; 5) The society could get a solution through the difficulty of gained the green feed in dry season; and 6) The society begins developing silage technology by their self. This program could be conducted well as which has been planned, and generally it could be said that the program is successful as the purposes of the program.